Secondary Syphilis in the Second Trimester Pregnancy : Case Report - Wibisono Nugraha; Eka Devinta Novi Diana; Frieda; Alfina Rahma; Prasetyadi Mawardi (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Syphilis is a sexually transmitted disease caused by Treponema pallidum, which is transmitted through sexual contact, blood transfusion and transplacental from an infected mother to the fetus. Syphilis in pregnancy can cause complications including abortion, low birth weight, premature birth, neonatal death or congenital syphilis infection.Case: A 39-year-old woman, 16 weeks pregnant, presented with a complaint of a small lump on the genitals accompanied by red patches on the palms of the hands and feet. Serological tests showed a reactive VDRL of 1:512 and a reactive TPHA of 1:640. Based on the history, physical examination and serological tests the patient was diagnosed with secondary syphilis in pregnancy. The management of this patient was given a single dose of Benzathine Penicillin G injection of 2.4 million units intramuscularly.Conclusion: Early screening for syphilis in pregnancy isvery important to prevent complications in the fetus. VDRL serological test examination 3 months after therapy was carried out to determine the success of therapy. In this case, there was a decrease in the VDRL titer to 1:4 in the absence of skin lesions 3 months after therapy with benzathine penicillin G 2.4 million units intramuscularly single dose.